Sparse production but preferential incorporation of recently produced naïve T cells in the human peripheral pool - Vrisekoop, Nienke (National Academy of Sciences, 2008)
In mice, recent thymic emigrants (RTEs) make up a large part of the naïve T cell pool and have been suggested to be a distinct short-lived pool. In humans, however, the life span and number of RTEs are unknown. Although (2)H(2)O labeling in young mice showed high thymic-dependent daily naïve T cell production, long term up- and down-labeling with (2)H(2)O in human adults revealed a low daily production of naïve T cells. Using mathematical modeling, we estimated human naïve CD4 and CD8 T cell half-lives of 4.2 and 6.5 years, respectively, whereas memory CD4 and CD8 T cells had half-lives of 0.4 and 0.7 year. The estimated half-life of recently produced naïve T cells was much longer than these average half-lives. Thus, our data are incompatible with a substantial short-lived RTE population in human adults and suggest that the few naïve T cells that are newly produced are preferentially incorporated in the peripheral pool.